2020
DOI: 10.1787/503bcecb-en
|View full text |Cite
|
Sign up to set email alerts
|

The changing labour market for graduates from medium-level vocational education and training

Abstract: Working Papers describe preliminary results or research in progress by the author(s) and are published to stimulate discussion on a broad range of issues on which the OECD works. Comments on Working Papers are welcomed, and may be sent to els.contact@oecd.org. This series is designed to make available to a wider readership selected labour market, social policy and migration studies prepared for use within the OECD. Authorship is usually collective, but principal writers are named. The papers are generally avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The universities also stand to benefit through "valorisation" activities, including the commercialisation of research outcomes. However, academics consider a lack of private and public funding for collaborative research, including from universities themselves, and the focus on producing practical results by businesses as barriers to collaboration, according to opinion surveys (University-Business Cooperation in Europe, 2018 [27]). The workload and bureaucracy related to collaborative research explains in part a comparatively low absorption capacity among SMEs.…”
Section: Enhancing Technology Transfer Through Stronger Collaborative...mentioning
confidence: 99%
“…The universities also stand to benefit through "valorisation" activities, including the commercialisation of research outcomes. However, academics consider a lack of private and public funding for collaborative research, including from universities themselves, and the focus on producing practical results by businesses as barriers to collaboration, according to opinion surveys (University-Business Cooperation in Europe, 2018 [27]). The workload and bureaucracy related to collaborative research explains in part a comparatively low absorption capacity among SMEs.…”
Section: Enhancing Technology Transfer Through Stronger Collaborative...mentioning
confidence: 99%
“…Going forward, technological change and increased digitalisation is a major challenge for vocational and educational training (VET) systems as it alters patterns of demand for both technical skills and key competencies. Technological progress puts a number of jobs at risk of disappearing due to automation (Vandeweyer and Verhagen, 2020), while creating new job opportunities. With workers likely to change tasks and occupation more frequently over a longer work-life span, a strong grounding of cognitive skills becomes more important.…”
Section: Figure 20 Performance In Reading Varies Widely Across Socio-...mentioning
confidence: 99%
“…To some extent, the Swiss VET system is well-positioned to address this challenge as a number of extensions of the curriculum and flexible education pathways offer opportunities to vocational students to gain higher qualifications including through tertiary education. As a result, about one third of young VET graduates work in high-skill occupations, a share significantly above the European average of 18% (Vandeweyer et al, 2020). However, a majority of apprentices do not choose the path to tertiary education and overly narrow specialisation of VET students could become a concern.…”
Section: Figure 20 Performance In Reading Varies Widely Across Socio-...mentioning
confidence: 99%
See 1 more Smart Citation
“…A review on entrepreneurship and innovation in higher education in Slovenia found that half of HEIs have put in place recruitment policies to attract international staff, while nearly all have internationalisation as a priority in their written strategies (Figure 36) (OECD/EU, 2021 [30]). A good example of the implementation of the internationalisation strategy is the University of Ljubljana, which has several bachelor and master degree programmes in English (University of Ljubljana, 2022) (University of Ljubljana, 2022 [80]). In addition, the doctoral school has 21 doctoral degree programmes in different fields open to Slovenians and external applicants (EU and non-EU members).…”
Section: Box 10 Internationalisation Of Higher Education Is Hampered ...mentioning
confidence: 99%